TEACHING AND LEARNING OF OLD AGE CARE AND SELF CARE: THE “AULA UNIVERSITARIA” EXPERIENCE - Zea Herrera, María del Carmen (Investigación y Educación en Enfermería, 2009)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> The “Aula Universitaria de Mayores” is an extracurricular proposal to answer the educational requirements of old age people from the life-health-illness perspective. Objectives: the principal aspects of the “Aula Universitaria de Mayores” program experience show that it has enabled for more than two years the training of 120 people with satisfactory assessment and approval within the Medellín and Metropolitan Area adult population. Conclusions: despite the popular saying that “old birds do not learn to sing” that would exclude them from university spaces, it is well known that old people retain repertories to defend themselves in daily life. Their education challenges the professionals; but is important to conceive it as a necessity, a right and a social service.